Exergetic analysis of different water depths evacuated tubessolar still. Issue 1 (15th August 2021) - More, Sunil; Daniel, Joseph
Abstract: The paper presents an energy and exergetic analysis of simple and evacuated tubes solar still. Experimental analysis was carried out on a 1 m 2 basin area and a total of 18 evacuated tubes are attached to the lower side of the solar still. The results revealed that the highest exergetic efficiency of 70.8% and 34.6% was achieved in 0.03 m water depth passive and active solar still, respectively. The work is also focused on the evaluation of the exergy destruction in the basin liner, water, and the glass cover of the solar still. The maximum exergy destruction rate was found in the basin liner and the minimum is found in the glass cover for both simple and evacuated tube solar still for all water depths. The maximum exergy destruction of 3068 and 5129 W/m 2 was observed in the basin liner of 0.05 m water depth simple and evacuated tube solar still.